Tissue-restricted expression of Nrf2 and its target genes in zebrafish with gene-specific variations in the induction profiles. - Hitomi Nakajima; Yaeko Nakajima-Takagi; Tadayuki Tsujita; Shin-Ichi Akiyama; Takeshi Wakasa; Katsuki Mukaigasa; Hiroshi Kaneko; Yutaka Tamaru; Masayuki Yamamoto; Makoto Kobayashi (PLoS ONE)
The Keap1-Nrf2 system serves as a defense mechanism against oxidative stress and electrophilic toxicants by inducing more than one hundred cytoprotective proteins, including antioxidants and phase 2 detoxifying enzymes. Since induction profiles of Nrf2 target genes have been studied exclusively in cultured cells, and not in animal models, their tissue-specificity has not been well characterized. In this paper, we examined and compared the tissue-specific expression of several Nrf2 target genes in zebrafish larvae by whole-mount in situ hybridization (WISH). Seven zebrafish genes (gstp1, mgst3b, prdx1, frrs1c, fthl, gclc and hmox1a) suitable for WISH analysis were selected from candidates for Nrf2 targets identified by microarray analysis. Tissue-restricted induction was observed in the nose, gill, and/or liver for all seven genes in response to Nrf2-activating compounds, diethylmaleate (DEM) and sulforaphane. The Nrf2 gene itself was dominantly expressed in these three tissues, implying that tissue-restricted induction of Nrf2 target genes is defined by tissue-specific expression of Nrf2. Interestingly, the induction of frrs1c and gclc in liver and nose, respectively, was quite low and that of hmox1a was restricted in the liver. These results indicate the existence of gene-specific variations in the tissue specificity, which can be controlled by factors other than Nrf2.